13C and 15N solid-state NMR studies on albendazole and cyclodextrin albendazole complexes - Ferreira, M. João G. (2015)
13C and 15N solid-state nuclear magnetic resonance (NMR) spectra were recorded from albendazole (ABZ) and from ABZ:β-cyclodextrin, ABZ:methyl-β-cyclodextrin, ABZ:hydroxypropyl-β-cyclodextrin and ABZ:citrate-β-cyclodextrin, which were prepared by the spray-drying technique. ABZ signals were typical of a crystalline solid for the pure drug and of an amorphous compound obtained from ABZ:cyclodextrin samples. Relevant spectral differences were correlated with chemical interaction between ABZ and cyclodextrins. The number and type of complexes revealed a strong dependence on the cyclodextrin group substituent. Solid-state NMR data were consistent with the presence of stable inclusion complexes.